2006
DOI: 10.1007/s00464-005-0230-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new basic virtual reality simulator for training of basic endoscopic skills

Abstract: Content, face, and concurrent validity of the SIMENDO is established. The simulator is considered useful for training eye-hand coordination for endoscopic surgery. The evaluated task could discriminate between the skills of experienced surgeons and novices, giving the first indication of construct validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 29 publications
3
56
1
Order By: Relevance
“…Moreover, they are capable of performing unsupervised assessment of trainees in a whole range of efficiency and quality parameters. Nevertheless, these studies are in many cases scarce, and others report negative [124][125][126] or inconclusive results [77]. This is often the case considering the high variability between studies, concerning participants, definition of surgical levéis, and in general the experiments' contour conditions (previous training in the system, number of repetitions allowed, etc.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they are capable of performing unsupervised assessment of trainees in a whole range of efficiency and quality parameters. Nevertheless, these studies are in many cases scarce, and others report negative [124][125][126] or inconclusive results [77]. This is often the case considering the high variability between studies, concerning participants, definition of surgical levéis, and in general the experiments' contour conditions (previous training in the system, number of repetitions allowed, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…The different VR simulators identified for this review are shown in Table 5 , [64][65][66][67][68][69][70][71][72][73][74][75][76][77]. VR simulators can be differenced by the way they make use of their didactic resources (Fig.…”
Section: Tracking Systems In Virtual Reality Simulatorsmentioning
confidence: 99%
“…Previously, the face and content validity of this simulator was established for the single-instrument exercises, and the first results for construct validity were shown [16]. The SIMENDO is a low-fidelity VR simulator developed to train basic endoscopic skills, such as eye-hand coordination, with the use of abstract tasks.…”
Section: Methodsmentioning
confidence: 99%
“…2). Previously, the usefulness and face validity of this simulator with a single instrument was studied [16].…”
Section: Materials and Techniquesmentioning
confidence: 99%